Metabolism of benzene in human liver microsomes: individual variations in relation to CYP2E1 expression - Nedelcheva, V; Gut, I; Soucek, P; Tichavská, B; Týnkova, L; Mráz, J; Guengerich, F P; Ingelman-Sundberg, M (Archives of toxicology, 1999)
In human liver microsomes the oxidations of benzene, chlorzoxazone, aniline, dimethylformamide, and 4-nitrophenol were significantly correlated with each other and with the level of cytochrome P450 (CYP) 2E1 estimated by immunoblotting. Moreover, benzene oxidation to water-soluble metabolites was suppressed by 0.1 mM diethyldithiocarbamate, supposedly a specific inhibitor of CYP2E1 at this level. None of these metabolic rates correlated with immunochemically determined levels of CYP1A2, 2C9, and 3A4 nor oxidation of 7-ethoxyresorufin, tolbutamide, and nifedipine. Benzene oxidation to water-soluble metabolites was characterized by typical Michaelis-Menten kinetics. The different benzene K(m) values seen in individual human microsomal samples were not correlated with the level or activity of CYP1A2, 2C9, 2E1, and 3A4 but could be due to CYP2E1 microheterogeneity. The lowest K(m) for benzene oxidation could be related to C/D and/or c1/c2 polymorphism of CYP2E1 gene. Covalent binding of benzene reactive metabolites to microsomal proteins was also correlated with the CYP2E1 metabolic rates and immunochemical levels. At high concentrations of benzene covalent binding was inversely related to benzene concentrations (as well as to formation of water-soluble metabolites) in agreement with the view that secondary metabolites, mainly benzoquinone, are responsible for the covalent binding.
Keywords: kinetika; Microsomes, Liver; Ditiocarb; Methane; genotyp; radioizotopy uhlíku; substrátová specifita; Genotype; voda; Glutathione; imunoblotting; chelátory; benzen; Water; Oxidation-Reduction; methan; Immunoblotting; Humans; Benzene; glutathion; dithiokarb; Kinetics; Substrate Specificity; jaterní mikrozomy; Chelating Agents; oxidace-redukce; Solubility; Carbon Radioisotopes; Cytochrome P-450 CYP2E1; cytochrom P-450 CYP2E1; rozpustnost; lidé